2021
DOI: 10.1186/s42836-021-00099-z
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term outcomes of tantalum cup– a single centre study

Abstract: Introduction The cementless acetabular implants are commonly used in primary and revision hip arthroplasty. Reconstruction of acetabulum in case of bone defects can be challenging. The aims of this single center study are to review the mid-term outcomes of porous tantalum cups (TM) and evaluate complications. Methods The midterm outcome of a trabecular metal tantalum modular uncemented cup was evaluated in 59 hips in 58 patients. In our group, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Lakstein et al reported a similar survivorship of 96%, including improved patient-reported outcomes in a series of 53 cases of revision THA using trabecular metal acetabular shells [3]. In a more recent study, Bawale et al reported a 96.0% implant survivorship in a 7.2 year follow-up of 41 revision THAs using tantalum porous metal implants [7]. Hosny et al reported an acetabular shell aseptic survivorship of 98.4% at a mean follow-up of 87.6 months in 62 cases of rTHA using a titanium highly porous multihole acetabular shell [8].…”
Section: Introductionmentioning
confidence: 92%
“…Lakstein et al reported a similar survivorship of 96%, including improved patient-reported outcomes in a series of 53 cases of revision THA using trabecular metal acetabular shells [3]. In a more recent study, Bawale et al reported a 96.0% implant survivorship in a 7.2 year follow-up of 41 revision THAs using tantalum porous metal implants [7]. Hosny et al reported an acetabular shell aseptic survivorship of 98.4% at a mean follow-up of 87.6 months in 62 cases of rTHA using a titanium highly porous multihole acetabular shell [8].…”
Section: Introductionmentioning
confidence: 92%
“…Finally, 67 articles were selected after full-text evaluation for eligibility. Table 2 provides a summary of the 67 rTHA studies (28,414 hips) showing the studies' characteristics and outcomes [ 12 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [82] , [83] , [84] ]. The stud...…”
Section: Resultsmentioning
confidence: 99%
“… TM augments 3 Xiao 2021 [ 22 ] Retrospective cohort Acetabular revision with porous Ta augments and titanium-coated cups 41 Aseptic loosening = 33 Periprosthetic infection = 8 122.8 (69-165) 0 (0%) 0 (0%) 0 (0%) The combination of Ta augments and conventional titanium-coated cups achieved satisfactory long-term radiographic and clinical outcomes for Paprosky type III acetabular bone defects without pelvic discontinuity. Ta augment 4 Bawale 2021 [ 23 ] Retrospective cohort TM Ta modular uncemented cup 59 hips (58 patients) Aseptic loosening = 35 (60.3%) Femoral loosening = 7 (11.8%) Fracture = 7 (11.8%) Cup Mal-alignment = 5 (8.8%) Infection = 2 (3.3%) Metal-on-metal related pathology = 3 (4%) 87 (24-144) 2 (3.2%) 1 (1.6%) - The use of Ta acetabular components during revision THA is associated with a lower incidence of infection (infection rate of 1.6% for deep infection) Ta cup 5 Simon 2021 [ 24 ] Case report TM augment for proximal metaphyseal femoral defect in rTHA 3 Osteolysis = 1 Periprosthetic fracture = 1 PJI = 1 15.8 0 0 - For severe proximal femur bone defects, Ta cones may be used for metaphyseal bone reconstruction. TM augment 6 Miettinen 2020 [ 68 ] Retrospective cohort Ta metal acetabulum component 100 Loosening of acetabulum = 67 linear wearing = 19 loosening of both components = 5 infection = 2 semiendoprothesis penetration through acetabulum = 2 component malposition with pain = 2 Periprosthetic fracture = 1 Loosening femur = 1 Recurrent dislocation = 1 11.5 ± 4.118 y 18 (18%) 6 (6%) The TM acetabular component gives excellent outcomes regarding stability and fixation to the acetabulum in acetabulum revision hip arthroplasty at a minimum of 10 y of follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Two cases with minor complications were registered in our study in Group A, one case of delayed wound healing and one case of lymphangitis (p = 0.21), while radiological evaluation at the final follow-up did not show any signs of polyethylene wear, radiolucency, septic or aseptic loosening, or change in alignment in both groups. Periprosthetic joint infection remains one of the most devastating complications of joint replacement surgery, and it constitutes an economic burden, both on patients and on society; the potential of using antibiotic-infused bone cement in primary cemented fixation may be an argument for its clinical superiority, but it must be underlined that tantalum components are associated with a lower incidence of infection [7,20]. In fact, in our experience, we have not found cases of periprosthetic infection; nevertheless, a recent review has demonstrated no significant difference in infection rates between cemented and cementless fixation, a finding supported by other systematic reviews [11].…”
Section: Discussionmentioning
confidence: 99%
“…The use of porous metals, such as titanium and tantalum, has led to greater coefficient of friction and a reduction in Young's modulus mismatch of the surface between the host bone and the implant [6]. Tantalum shows excellent compatibility from a biological perspective: its ability to form a self-passivating surface oxide layer leads to the formation of a bone-like apatite coating, resulting in excellent bony ingrowth, allowing rapid and substantial bone attachment, and avoiding the unsatisfactory results of first-generation designs [5][6][7].…”
Section: Introductionmentioning
confidence: 99%